Gender Wage Gap Analysis in Riau Province Using the Blinder-Oaxaca Decomposition Method - Maulida, Yusni; Ningsih, Rahmita Budiarti; Indrawati, Toti; Widayatsari, Any; Karneli, Okta (Journal of Ecohumanism, 2024)
This study investigates the gender wage gap in Riau Province using the Blinder-Oaxaca decomposition method to examine its underlying factors. The analysis reveals a significant wage disparity, where women earn, on average, 29.56% less than men, despite higher educational attainment among women. The decomposition results highlight that only 2.44% of the gap is explained by observable factors such as education and employment type, while 76.76% remains unexplained, indicating the prevalence of discrimination and unmeasured structural barriers. This study identifies unique regional dynamics, including the paradox of women in urban areas earning less than their rural counterparts, contrary to global trends. Additionally, the study underscores the role of formal employment in reducing wage disparities, with women in formal jobs earning significantly more than those in informal sectors. These findings suggest that while improving education and transitioning women into formal employment can partially address wage disparities, structural reforms targeting workplace discrimination and cultural norms are essential for achieving gender wage equity. The study contributes to the literature by providing localized insights into gender wage gaps in Riau Province, emphasizing the need for targeted policy interventions to enhance equity in labor market outcomes.